Pengaruh Kedisiplinan Belajar terhadap Prestasi Belajar Bahasa Indonesia pada Siswa Sekolah Dasar - Hasan, Hasan; Putra, Angga; M. Amin, M. Amin; Astuti, Kartika Puji (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2024)
Class V students at SD Negeri 14 Woja still lack discipline in studying. When they study at school, there are still those who are late for school, don't do their assignments well, don't pay attention to the lessons taught by the teacher, and lack readiness in following lessons. This results in less effective learning so that children cannot absorb the material provided by the teacher properly. Based on the background above, this research aims to determine the influence of learning discipline at school on the Indonesian language learning achievement of Class V students at SDN 14 Woja, Dompu Regency, 2016/2017 academic year. This research includes correlation research with a quantitative approach. Based on the results of the data analysis above, it can be concluded that there is an influence of learning discipline at school on the learning achievement of class V students at Dompu State Elementary School for the 2016/2017 academic year. This can be seen from the results of the V data analysis of the questionnaire with a significance level of 0.05% or 5% and n-2 = 23, obtained T table = 0.714. This result shows that T count = 2.966 t table = 0.714 (one party test with interpolation). In this case, the condition applies that, t calculated is smaller and/or equal to t table, then HO is accepted. It turns out that the calculated T is greater than the t table (2.966≥ 0.714), so Ho is rejected and Ha is accepted, which means there is a real (significant) influence between variable (X) and variable (Y).